Tin-free visible light photoredox catalysed cyclisation of enamides as a mild procedure for the synthesis of γ-lactams. Issue 16 (13th July 2016) - Fava, Eleonora; Nakajima, Masaki; Tabak, Martin B.; Rueping, Magnus
Abstract : A visible light mediated tin-free 5- endo-trig cyclisation of α-chloroenamides, leading to synthetically valuable γ-lactams in good yields and high diastereomeric ratios, was developed. Abstract : The first visible light mediated tin-free cyclisation of α-chloroenamides leading to the synthesis of substituted γ-lactams with excellent stereoselectivity is reported. The protocol employs the single-electron reduction of activated C–Cl bonds, which are typically inert towards reduction.